Advances in Computational Intelligence First International Conference, ICACI 2023, Hyderabad, India, December 15-16, 2023, Proceedings - Venu Gopal Rao, K.; Krishna Prasad, A. V.; Vijaya Bhaskar, Seelam Ch.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This book constitutes the refereed proceedings of the First International Conference on Advances in Computational Intelligence, ICACI 2023, held in Hyderabad, India, during December 15-16, 2023. The 7 full papers and 2 short papers included in this book were carefully reviewed and selected from 234 submissions. These papers focus on the diverse applications of Data engineering in various areas such as Data Mining, Artificial Intelligence, Natural Language Processing, Pattern Recognition, and Machine Learning.
-- Smart Helmet. -- Brain Tumor Detection Using CNN. -- An Efficient Machine Learning Enabled Algorithm to Predict Student Performance in Higher Education. -- Accelerating Neural Network Model Deployment with Transfer Learning Techniques using Cloud Edge - Smart IoT Architecture. -- Machine Learning Revolutionizing in Gestational Diabetes Care. -- Detection of Malwares on Android Devices Using A Genetic Algorithm - Based Feature Selection And Machine Learning. -- Deep Learning - Based Health Care System Using Chest X - Ray Scans for Image Classification. -- Advancements and Challenges in Text Summarization: An Overview of Methods and Strategies in Brief. -- A Novel Methodology to Predict and Detect the Consumption of Power for Smart Commercial Areas using Stacked GRU and LSTM (called Deep GRULS Architecture).
Keywords: Data mining; Computational intelligence; Artificial intelligence -- Data processing; Artificial intelligence; Data Mining and Knowledge Discovery; Computational Intelligence; Data Science; Artificial Intelligence